2016
DOI: 10.5455/msm.2016.28.343-347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patients' Admission, Mean and Highest Sofa Scores in Prediction of ICU Mortality: a Prospective Observational Study

Abstract: Background:Use of valid criteria for evaluation of patients admitted to intensive care unit (ICU) is essential to assess the quality of services provided. This study was conducted to evaluate admission, mean and the highest Sequential Organ Failure Assessment (SOFA) scores in predicting mortality and outcome of patients admitted to the ICU.Methods:This prospective observational study was conducted on 300 patients admitted to the ICU of Imam Khomeini Hospital, Sari, Iran, in 2015. The SOFA tool was applied at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
11
1
1
Order By: Relevance
“…SOFA score had the highest accuracy and predictive ability followed by APACHE II score while serum amylase was the least one. This was in agreement with Baradari et al (2016) and Shabir and Maqbool, (2017) "SOFA score is able to predict outcome significantly". Kim et al (2013) concluded that SOFA score is more useful in predicting mortality, and easier and simpler than APACHE II score.…”
Section: Discussionsupporting
confidence: 90%
“…SOFA score had the highest accuracy and predictive ability followed by APACHE II score while serum amylase was the least one. This was in agreement with Baradari et al (2016) and Shabir and Maqbool, (2017) "SOFA score is able to predict outcome significantly". Kim et al (2013) concluded that SOFA score is more useful in predicting mortality, and easier and simpler than APACHE II score.…”
Section: Discussionsupporting
confidence: 90%
“…interventions, and may account for the difference between our two populations [25]. The poor performance of delta-SOFA at 48-hours for mortality prediction despite 48-hour SOFA's good discrimination in our cohort may be attributed to the predominance of unchanged high SOFA scores at 48 hours, [18,19,26]. Our second objective was to identify factors associated with higher risk of mortality among critically ill patients in a well-resourced private ICU in a lower middle-income country.…”
Section: Plos Onementioning
confidence: 92%
“…The Eastern Cooperative Oncology Group (ECOG) Performance Status was used to assess performance status in the month to fourteen days before the ICU admission (20). To evaluate the extent of the acute critical illness of the patients at ICU admission, the Sequential Organ Failure Assessment (SOFA) score was used (21,22). The SOFA score is seen as an useful predictor of outcome (23).…”
Section: Methodsmentioning
confidence: 99%